2005
DOI: 10.1111/j.1365-2036.2005.02558.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in acute and maintenance treatment of non‐erosive and mild erosive gastro‐oesophageal reflux disease

Abstract: Summary Background:  Quality of life has been assessed in a large, multicentre randomized, open label study. Aim:  To evaluate the economic and clinical consequences of two different maintenance treatment modalities, administered to 6017 gastro‐oesophageal reflux disease patients at 451 gastroenterological centres in Italy. Methods:  Adult gastro‐oesophageal reflux disease patients received, at enrolment, an acute treatment of esomeprazole 40 mg/day for 4 weeks and, if successfully treated, were randomized int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 25 publications
3
41
1
4
Order By: Relevance
“…12,14,15 Although HRQoL improves with treatment, persistent symptoms after PPI therapy are associated with a reduced HRQoL. 14,16,17 However it is unclear how the recurrence of GERD symptoms impacts patients' HRQoL. Furthermore, there have been no reports regarding the difference in the impact of relapsed GERD symptoms on HRQoL between patients with erosive reflux disease (ERD) and non-erosive reflux disease (NERD).…”
Section: Introductionmentioning
confidence: 99%
“…12,14,15 Although HRQoL improves with treatment, persistent symptoms after PPI therapy are associated with a reduced HRQoL. 14,16,17 However it is unclear how the recurrence of GERD symptoms impacts patients' HRQoL. Furthermore, there have been no reports regarding the difference in the impact of relapsed GERD symptoms on HRQoL between patients with erosive reflux disease (ERD) and non-erosive reflux disease (NERD).…”
Section: Introductionmentioning
confidence: 99%
“…The level of quality of life in reflux disease was comparable to that observed in mild-degree heart failure [18]. Also, the analyses conducted in Italy, China, Japan, and Australia confirmed that the HRQOL of GERD patients is markedly lower as compared to the general populations of those countries [14,[19][20][21].…”
Section: Quality Of Life In Patients With Gastroesophageal Reflux Dismentioning
confidence: 67%
“…Usually the treatment with PPIs lasts for 2 to 8 weeks [14]. No significant differences were observed between various medications from this group [35], but it should be mentioned that PPIs proved more effective than H2-receptor antagonists [13,35].…”
Section: Influence Of Pharmacotherapy On the Quality Of Lifementioning
confidence: 77%
See 1 more Smart Citation
“…Although disease progression may be a concern in GERD, the number of patients who progress through Barrett's esophagus to esophageal cancer appears to be very small [3]. Despite the low risk for progression to severe disease, clinical trials suggest that the use of on-demand or intermittent antireflux medication can improve quality of life and may regress GERD in response to treatment with these modalities [13][14][15][16]. For example, in one clinical study, symptoms of GERD remained improved after six months in 80.2% and 77.8% of patients who had been randomly assigned to continuous (n=658) and on demand (n=634), respectively following four weeks of once daily medication.…”
Section: Consequences Of Untreated Acid-related Gastrointestinal Disomentioning
confidence: 99%